Effect of Brand Coverage in Social-Media on Customer Value Creation: A Study of Tourist-based Restaurants in Nepal - Sthapit, Arhan; Shrestha, Bikash; Hamal, Sadikshya (Profesional Muda Cendekia Publishing, 2023)
Purpose: The paper aimed to examine the impact of the Nepalese tourist-based restaurants’ brand coverage in their social media on customer value creation. Methodology/Design/Approach: A questionnaire survey was administered on 205 tourist customers (with usable response of 196) intercepted at ten tourist-based restaurants located at one of the popular tourist-restaurant hubs of the Kathmandu Valley, in the post-COVID months of March and April of 2023. It made use of the descriptive statistics and inferential ones like Levenes’ test of equality of error variances, Wilks' Lambda test and MANCOVA test. Findings: The study found that the use of social media in marketing tourist-based restaurants helped create customer value, as social media marketing made a substantial and positive impact on the creation of social, functional, and economic values of tourist-based restaurants. Originality of the research: The study specifically discusses the tourist-based restaurants’ brand coverage in their social media and investigates its impact on customer value creation at a time when Nepalese tourism has started gradually recovering from the consequences of the COVID-19 pandemic. It is the first study of this kind at least in the Nepalese context.